Job Satisfaction In Organization: A Systematic Literature Review - Wiara Sanchia Grafita Ryana Devi; Ferry Arfiansyah; Nurul Afifah; Rengga Madya Pranata (Innovative: Journal Of Social Science Research, 2023)
Employee and job satisfaction has been major research in management studies throughout the world. It is the main concern for organizations to measure the performance of individuals. Employee performance at work is measured by how they carry out their responsibilities in a manner that contributes to the achievement of the organization's goals and creates satisfaction feeling in their work. This study employed a Systematic Literature Review (SLR) methodology which combined several previous studies to be analyzed. The preliminary studies were obtained and selected based on the article which published in a reputable journal such as the Scopus database index. Significant findings summarize the result that researchers have noted that employees' attitudes and performance at work are influenced by how satisfied they are with their jobs. In conclusion, this systematic literature review study provides an overview of current research on job satisfaction and employee relations. A total of 24 publications of the article were analyzed in this systematic literature review. Firstly, the majority of factors that determine job satisfaction are HRM, employee relationship, and workplace that most frequently suggested in the articles. Secondly, the most suggested ways to increase employees’ job satisfaction that are discussed in many articles are job performance, job security and leadership.